2022
DOI: 10.1002/mrm.29465
|View full text |Cite
|
Sign up to set email alerts
|

A method for measuring B0 field inhomogeneity using quantitative double‐echo in steady‐state

Abstract: To develop and validate a method for B 0 mapping for knee imaging using the quantitative Double-Echo in Steady-State (qDESS) exploiting the phase difference (Δ𝜃) between the two echoes acquired. Contrary to a two-gradient-echo (2-GRE) method, Δ𝜃 depends only on the first echo time.Methods: Bloch simulations were applied to investigate robustness to noise of the proposed methodology and all imaging studies were validated with phantoms and in vivo simultaneous bilateral knee acquisitions. Two phantoms and five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Recent works have shown that the DESS sequence can be used for B 0 mapping 10 . Reconstructing one B 0 map and one T 2 map per respiratory phase could potentially improve the accuracy of the T 2 estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent works have shown that the DESS sequence can be used for B 0 mapping 10 . Reconstructing one B 0 map and one T 2 map per respiratory phase could potentially improve the accuracy of the T 2 estimates.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 Recent works have shown that the DESS sequence can be used for B 0 mapping. 10 Reconstructing one B 0 map and one T 2 map per respiratory phase could potentially improve the accuracy of the T 2 estimates. Indeed, the gold standard spin-echo sequence provides longer T 2 values in GM and WM regions than the current protocol, [45][46][47] which is not the case for phantom experiments (details in Table S1 F I G U R E 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New extensions of DESS sequences have appeared in the study by Zijlstra et al, 77 with the proposal of a new sequence called multiple‐echo steady‐state (MESS) to jointly produce T 2 mapping and water–fat separation with chemical‐shift correction. It was shown that quantitative DESS (qDESS) could be used to measure B 0 field inhomogeneity 78 . The diagnostic quality of a 5‐minute (min) sequence based on qDESS was evaluated to detect knee joint pathology, showing high interreader agreement between the new 5‐minute sequence and a conventional 20‐minute MRI 60 .…”
Section: Emerging Methods For Quantitative Mri For Cartilagementioning
confidence: 99%
“…It was shown that quantitative DESS (qDESS) could be used to measure B 0 field inhomogeneity. 78 The diagnostic quality of a 5-minute (min) sequence based on qDESS was evaluated to detect knee joint pathology, showing high interreader agreement between the new 5-minute sequence and a conventional 20-minute MRI. 60 Figure 7 illustrates some of the images obtained in the study.…”
Section: Updates On Improved Rf Pulse Sequences and Sequence Optimiza...mentioning
confidence: 99%